Kinerja Marshall Immersion pada Campuran Asphalt Concrete Wearing Course (AC-WC) dengan Penambahan Cangkang Sawit sebagai Substitusi Agregat Halus - Mukhlis, Mukhlis; Lusyana, Lusyana; Suardi, Enita; Adibroto, Fauna (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2018)
Asphalt concrete wearing courses (AC-WC) are asphalt mixtures which consist of coarse and fine aggregates plus fillers which have a continuous gradation with asphalt binder. In general, the aggregates in the AC WC mixtures consist of natural rock materials which are broken down and in certain areas the availability is limited so it must be imported from other regions. This resulted in relatively high prices from the asphalt mixture. This can be anticipated by looking for alternative aggregate substitute materials, one alternative is to use palm oil shells. In this test, palm shells were used as a substitute for fine aggregates with variations in percentage of palm shells, namely 0%, 5%, 10%, 15%, 20%, 25%, the tests were carried out namely the testing of volumetric characteristics, Marshall characteristics, determination of optimum asphalt content and Marshall immersion. From the results of the study obtained the value of Marshall Immersion decreases as the percentage of palm shells increases in the mixture.